ANALISIS DAYA SAING DAERAH ANTAR KECAMATAN KOTA PEKANBARU - Hutabarat Supriadi; Hamidi Wahyu; Kornita Endang Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the competitiveness of institutional variables, socio-politics, regional economies, productivity and labor and physical infrastructure. This is to determine the level of competitiveness between kecamtan in Pekanbaru City. This type of descriptive quantitative research. The population in this study were all people who were in the workforce age, namely 15 - 65 years and living in Pekanbaru City with a total population of 513,271 people. A sample of 12 people. The results of this study indicate that the regional competitiveness between districts that has the highest percentage of the regional economic variable is Sail sub-district. Furthermore, the physical infrastructure variable for Sail sub-district. Then for the variables of labor and productivity in Sail and Lima Puluh districts. Next, the institutional variables are Fifty and in the socio-political variables are in the Lima Puluh district. The ranks of the highest to lowest sub-districts are Payung Sekaki, Sail and Lima Puluh Subdistricts. This is due to the high contribution of Payung Sekaki, Sail and Fifty sub-districts in the fields of agriculture and processing industry. As the center of government for Payung Sekaki, Sail and Lima Puluh sub-districts, they have a high level of competitiveness, but what makes the region the second highest region is that good infrastructure is not accompanied by natural resources. Meanwhile, in terms of human resources, the ranking looks goodKeywords: Regional Economy, Physical Infrastructure, Labor and Productivity, Institutional, Socio-Political, Regional Competitiveness